Wilhelm Lautenbach's credit mechanics – a precursor to the current money supply debate. Issue 2 (4th March 2022) - Decker, Frank; Goodhart, Charles A. E.
Abstract: This article assesses the theory of credit mechanics within the context of the current money supply debate. Credit mechanics and related approaches were developed by a group of German monetary economists during the 1920s-1960s. Credit mechanics overcomes a one-sided, bank-centric view of money creation, which is often encountered in monetary theory. We show that the money supply is influenced by the interplay of loan creation and repayment rates; the relative share of credit volume neutral debtor-to-debtor and creditor-to-creditor payments; the availability of loan security; and the behaviour of non-banks and non-borrowing bank creditors. With the standard textbook models of money creation now discredited, we argue that a more general approach to money supply theory involving credit mechanics needs to be re-established.